Bipyrrole boomerangs via Pd-mediated tandem cyclization–oxygenation. Controlling reaction selectivity and electronic properties - Moshniaha, Liliia; Żyła-Karwowska, Marika; Cybińska, Joanna; Chmielewski, Piotr J.; Favereau, Ludovic; Stępień, Marcin (Beilstein Journal of Organic Chemistry, 2020)
Boomerang-shaped bipyrroles containing donor–acceptor units were obtained through a tandem palladium-mediated reaction consisting of a cyclization step, involving double C–H bond activation, and a double α-oxygenation. The latter reaction can be partly suppressed for the least reactive systems, providing access to α-unsubstituted boomerangs for the first time. These “α-free” systems are highly efficient fluorophores, with emission quantum yields exceeding 80% in toluene. Preliminary measurements show that helicene-like boomerangs may be usable as circularly polarized luminescent materials.
Keywords: donor–acceptor systems; double C–H bond activation; helicenes; pyrroles

Synthetic Methods for Conjugated Polymers and Carbon Materials - Narita, A. (Synthesis of Structurally Defined Nanographene Materials through Oxidative Cyclodehydrogenation, 2017)

(untitled) - Stępień, M.; Gońka, E.; Żyła, M.; Sprutta, N. (Chem. Rev., 2017)

(untitled) - Wang, X.-Y.; Yao, X.; Narita, A.; Müllen, K. (Acc. Chem. Res., 2019)

(untitled) - Grzybowski, M.; Sadowski, B.; Butenschön, H.; Gryko, D. T. (Angew. Chem., Int. Ed., 2020)

(untitled) - Sarhan, A. A. O.; Bolm, C. (Chem. Soc. Rev., 2009)

(untitled) - Grzybowski, M.; Skonieczny, K.; Butenschön, H.; Gryko, D. T. (Angew. Chem., Int. Ed., 2013)

(untitled) - Simpson, C. D.; Brand, J. D.; Berresheim, A. J.; Przybilla, L.; Räder, H. J.; Müllen, K. (Chem. – Eur. J., 2002)

(untitled) - Ormsby, J. L.; Black, T. D.; Hilton, C. L.; Bharat; King, B. T. (Tetrahedron, 2008)

(untitled) - Golling, F. E.; Quernheim, M.; Wagner, M.; Nishiuchi, T.; Müllen, K. (Angew. Chem., Int. Ed., 2014)

(untitled) - Chen, F.; Tanaka, T.; Osuka, A. (Chem. Commun., 2017)

(untitled) - Seifert, S.; Shoyama, K.; Schmidt, D.; Würthner, F. (Angew. Chem., Int. Ed., 2016)

(untitled) - Zhylitskaya, H.; Stępień, M. (Org. Chem. Front., 2018)

(untitled) - Navakouski, M.; Zhylitskaya, H.; Chmielewski, P. J.; Lis, T.; Cybińska, J.; Stępień, M. (Angew. Chem., Int. Ed., 2019)

(untitled) - Shoyama, K.; Würthner, F. (J. Am. Chem. Soc., 2019)

(untitled) - Myśliwiec, D.; Stępień, M. (Angew. Chem., Int. Ed., 2013)

(untitled) - Feng, C.-N.; Hsieh, Y.-C.; Wu, Y.-T. (Chem. Rec., 2015)

(untitled) - Matsuoka, W.; Ito, H.; Itami, K. (Angew. Chem., Int. Ed., 2017)

(untitled) - Daigle, M.; Picard-Lafond, A.; Soligo, E.; Morin, J.-F. (Angew. Chem., Int. Ed., 2016)

Synthetic Methods for Conjugated Polymers and Carbon Materials - Morin, J.-F.; Daigle, M.; Desroches, M. (Photochemical and Direct C–H Arylation Routes toward Carbon Nanomaterials, 2017)

(untitled) - Ozaki, K.; Kawasumi, K.; Shibata, M.; Ito, H.; Itami, K. (Nat. Commun., 2015)

(untitled) - Hassan, J.; Sévignon, M.; Gozzi, C.; Schulz, E.; Lemaire, M. (Chem. Rev., 2002)

(untitled) - Åkermark, B.; Eberson, L.; Jonsson, E.; Pettersson, E. (J. Org. Chem., 1975)

(untitled) - Hellwinkel, D.; Kistenmacher, T. (Liebigs Ann. Chem., 1989)

(untitled) - Stuart, D. R.; Fagnou, K. (Science, 2007)

(untitled) - Yeung, C. S.; Dong, V. M. (Chem. Rev., 2011)

(untitled) - Deng, Y.; Persson, A. K. Å.; Bäckvall, J.-E. (Chem. – Eur. J., 2012)

(untitled) - Rank, C. K.; Jones, A. W.; Wall, T.; Di Martino-Fumo, P.; Schröck, S.; Gerhards, M.; Patureau, F. W. (Chem. Commun., 2019)

(untitled) - Zhylitskaya, H.; Cybińska, J.; Chmielewski, P.; Lis, T.; Stępień, M. (J. Am. Chem. Soc., 2016)

(untitled) - Żyła-Karwowska, M.; Zhylitskaya, H.; Cybińska, J.; Lis, T.; Chmielewski, P. J.; Stępień, M. (Angew. Chem., Int. Ed., 2016)

(untitled) - Moshniaha, L.; Żyła-Karwowska, M.; Chmielewski, P. J.; Lis, T.; Cybińska, J.; Gońka, E.; Oschwald, J.; Drewello, T.; Rivero, S. M.; Casado, J.; Stępień, M. (J. Am. Chem. Soc., 2020)

(untitled) - Navakouski, M.; Zhylitskaya, H.; Chmielewski, P. J.; Żyła-Karwowska, M.; Stępień, M. (J. Org. Chem., 2020)

(untitled) - Żyła‐Karwowska, M.; Moshniaha, L.; Hong, Y.; Zhylitskaya, H.; Cybińska, J.; Chmielewski, P. J.; Lis, T.; Kim, D.; Stępień, M. (Chem. – Eur. J., 2018)

(untitled) - Żyła-Karwowska, M.; Moshniaha, L.; Zhylitskaya, H.; Stępień, M. (J. Org. Chem., 2018)

(untitled) - Vauthey, E. (ChemPhysChem, 2012)